Comparing measures of sparsity - Hurley, N.; Rickard, S. (2008 IEEE Workshop on Machine Learning for Signal Processing, 2008)
Sparsity is a recurrent theme in machine learning and is used to improve performance of algorithms such as non-negative matrix factorization and the LOST algorithm. Our aim in this paper is to compare several commonly-used sparsity measures according to intuitive attributes that a sparsity measure should have. Sparsity of representations of signals in fields such as blind source separation, compression, sampling and signal analysis has proved not just to be useful but a key factor in the success of algorithms in these areas. Intuitively, a sparse representation is one in which a small number of coefficients contain a large proportion of the energy. In this paper we discuss six properties (robin hood, scaling, rising tide, cloning, bill gates and babies) that we believe a sparsity measure should have. The main contribution of this paper is a table which classifies commonly-used sparsity measures based on whether or not they satisfy these six propositions. Only one of these measures satisfies all six: the Gini index.